The space cold atom interferometer for testing the equivalence principle in the China Space Station - Meng He; Xi Chen; Jie Fang; Qunfeng Chen; Huanyao Sun; Yibo Wang; Jiaqi Zhong; Lin Zhou; Chuan He; Jinting Li; Danfang Zhang; Guiguo Ge; et al. (npj Microgravity, 2023)
Abstract The precision of the weak equivalence principle (WEP) test using atom interferometers (AIs) is expected to be extremely high in microgravity environment. The microgravity scientific laboratory cabinet (MSLC) in the China Space Station (CSS) can provide a higher-level microgravity than the CSS itself, which provides a good experimental environment for scientific experiments that require high microgravity. We designed and realized a payload of a dual-species cold rubidium atom interferometer. The payload is highly integrated and has a size of $$460\,{\rm{mm}}× 330\,{\rm{mm}}× 260\,{\rm{mm}}$$ 460 mm × 330 mm × 260 mm . It will be installed in the MSLC to carry out high-precision WEP test experiment. In this article, we introduce the constraints and guidelines of the payload design, the compositions and functions of the scientific payload, the expected test precision in space, and some results of the ground test experiments.